Oil and Cars: The Impact of Crude Oil Prices on the Stock Returns of Automotive Companies - Lis, Bettina; Nessler, Christian; Retzmann, Jan (International Journal of Economics and Financial Issues, 2012)
In this paper we are testing whether the impact of oil prices is different on the overall market and automotive companies. In addition we investigate, if this relationship is nonlinear. For this we use stock return data of US, German and Japanese car companies, and returns of share indices from the same countries as control variables, and Brent crude oil price changes. We first estimate the impact of crude oil on the indices, then clean the indices from these influences, and afterwards estimate the impact on the stocks. For this we are using OLS and EGARCH (1,1). We conclude that in general the car companies‘ stocks do not react more adversely as the overall market to crude oil price increases, while Japanese companies do not show any excess sensitivity at all. German companies tend to be sensitive, and US and German companies are together more sensitive in the more recent time periods. Keywords: Crude oil; Automotive; Car producers; Stock returns; Regression; Nonlinear JEL Classifications: G12; G14